Relating Diffuse Interstellar Band Strengths to Line of Sight Properties. Issue Volume 9:Issue S297(2013) (21st February 2014) - Rashedi, H.; Cami, J.; Cox, N. L. J.; van Winckel, H.
Abstract: We present a preliminary analysis of a set of optical (3800-8800 Å) high resolution ( R = 80, 000) spectra for 69 diffuse interstellar band targets. We carried out a sensitive search for interstellar features in the wavelength range 8470-8740 Å that will be covered by the upcoming GAIA mission. We also investigate how the λ8620Å DIB strength varies as a function of other interstellar parameters (other DIBs, E(B-V) and atomic and molecular column densities).